A Study of Public Awareness towards Health Education and Social Issues in Developing Countries: A Graphical Representation of Social Issues in Nepal - Karna, Santosh Kumar; Sahani, Suresh Kumar; Mishra, Arjun Kumar; Sahani, Kameshwar; Thakur, Ambika Kumari (FONDATIA, 2024)
In this research paper, we have studied procedures applying for documentation and institutionalization of learning and good practices for policy advocacy replication scaling up and public awareness. It also consists issue regarding health consciousness toward chronic diseases about whom rural people are unaware of and don’t have understanding about the procedures of prevention.